State bounding for switched homogeneous positive nonlinear systems with exogenous input. (August 2018) - Zhang, Na; Sun, Yuangong; Meng, Fanwei
Abstract: This paper considers the state bounding problem for switched homogeneous positive nonlinear systems with bounded exogenous input. Both continuous-time switched positive nonlinear systems whose vector fields are homogeneous of degree one and cooperative, and discrete-time switched positive nonlinear systems whose vector fields are homogeneous of degree one and order preserving are discussed under average dwell time switching. By using a new method, we derive necessary and sufficient conditions for the existence of a ball where all the solutions of the system converge exponentially within. Numerical examples are also presented to illustrate the theoretical results.